The Nth amendment of the Tenth Additional Provision of the Workers’ Statute - Esteve Segarra, Amparo (LABOS Revista de Derecho del Trabajo y Protección Social, 2022)
The tenth additional provision of the ET has undergone constant changes in successive reforms. The latest version of the precept aims to prohibit forced retirements provided for in collective agreements below 68 years of age and establishes as the only justification for the employment policy the new hiring of a worker with an indeterminate contract and full time. In addition, a positive action measure is introduced to encourage the hiring of new workers to fill the jobs of forced retirees in sectors with low female employment, making it possible to lower the retirement age in the conventional clauses of forced retirement up to normal retirement age.